Stellar Cycle and Evolution of Polar Spots in an M+WD Binary - Zhao, Xinlin; Wang, Song; Li, Xue; Xiang, Yue; Xu, Fukun; Gu, Shenghong; Du, Bing; Liu, Jifeng (The Astrophysical journal, 2024)
Stellar activity cycles reveal continuous relaxation and induction of magnetic fields. The activity cycle is typically traced through the observation of cyclic variations in total brightness or Ca H&K emission flux of stars, as well as cyclic variations in the orbital periods of binary systems. In this work, we report the identification of a semidetached binary system (TIC 16320250) consisting of a white dwarf (0.67 M ⊙ ) and an active M dwarf (0.56 M ⊙ ). The long-term multiband optical light curves spanning twenty years revealed three repeated patterns, suggestive of a possible activity cycle of about 10 years of the M dwarf. Light-curve fitting indicates the repeated variation is caused by the evolution, particularly the motion, of polar spots. The significant Ca H&K, H α , ultra-violet, and X-ray emissions imply that the M dwarf is one of the most magnetically active stars. We propose that in the era of large time-domain photometric sky surveys (e.g., ASAS-SN, Zwicky Transient Facility, LSST, Sitian), long-term light-curve modeling can be a valuable tool for tracing and revealing stellar activity cycle, especially for stars in binary systems.